Percutaneous occlusion of large aneurysmal right coronary artery saphenous vein bypass graft - Kuliczkowski, Wiktor; Kusa, Jacek; Brzozowski, Piotr; Witkowska, Agnieszka; Bulak, Luiza; Reczuch, Krzysztof (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2021)
An 80-year-old man after a coronary artery bypass graft (CABG) in 2003 (LIMA-LAD, SVG-RCA, SVG-Dg) had a chest X-ray scan performed due to pulmonary infection which uncovered a mediastinal tumor. Using computed tomography SVG-RCA aneurysm consisting of two communicationg sacs (8.2 × 8.6 × 8.4 cm and 9.8 × 8.1 × 9.2 cm) were detected (Figures 1 A, B). The patient did not show any symptoms related to the aneurysm. The patient was consulted by the Heart Team in accordance with the literature regarding the risk of further enlargement or rupture of the aneurysms [1], and due to high risk of complications during sternotomy in the cardiosurgeons’ assessment the decision was taken to close the aneurysms percutaneously.